PENGARUH RETURN ON EQUITY (ROE), DEBT TO EQUITY RATIO (DER) DAN PRICE EARNINGS RATIO (PER) TERHADAP HARGA SAHAM - Dhesma Yana; Wulandari Agustiningsih (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to determine the effect of return on equity (ROE), debt to equity ratio (DER) and price earnings ratio (PER) on stock prices. The population using the food and beverage sub-sector companies for the 2016-2020 period amounted to 38 companies and the sample obtained was 14 companies using purposive sampling technique. The analysis in this study uses descriptive statistics, while the hypothesis testing uses multiple linear regression analysis. The results of this study indicate that there is a simultaneous influence between ROE, DER, and PER on stock prices. Partially ROE and PER have a positive and significant effect on stock prices. Meanwhile, DER has a negative and significant effect on stock prices.